Lypozyme treatment of coconut flour - Misador, Vyva V.
ABSTRACT This study was undertaken to reduce the fat content of coconut flour produced using the Modified Versoza process (Guantes, 1989). To carry out this reduction, enzyme lipozyme, which causes hydrolysis of oil, was employed. This enzyme was able to extract as much as 41.23% oil from the coconut cell after four (4) days of treatment. Maximum extractability was achieved aft three days of treatment and decreased beyond four days. The enzyme-treated coconut flour was then subjected to objective as well as subjective tests. The results obtained was compared against an untreated coconut flour to be able to determine the effect of enzyme treatment on the overall acceptability of the final product. The lipozyme-treated flour has a moisture content of 1%, 3.2% protein, 0.33% ash and crude fiber of 12.20%. The untreated coconut flour on the other hand, has 0.83% moisture content, 2.86% protein, ash of about 1.62%, 29.24% crude fiber and 26.59% fat content. In terms of sensory attributes, acceptability was greatly reduced especially in terms of color and odor characteristics in the enzyme-treated flour. Lipozyme-treated coconut flour was light brown in color while untreated flour was white and a distinct rancid odor was discernible. These are indicative of oil hydrolysis into fatty acids by the lipozyme enzyme.